Practicing diplomacy simulations, perspectives, and applications - Enverga, Manuel R. III; Tionloc, Javier Rico Israel R.; BlueBooks (Firm) (Quezon City BlueBooks, 2019)
This book is relevant to students and practitioners who are interested in learning about diplomacy. It moves beyond discussions of historical events and emphasizes real-life application and practice. Diplomacy is not a theoretical field, and as such, students that are interested in it would benefit from both experiences and simulations that would allow them to practice diplomatic skills. Simulations are particularly important and are used as a training tool for aspiring diplomats in Singapore, the United Kingdom, and the United States but seldom used in the Philippines. This resource can also be used in the training of Philippine diplomats, providing them information and skills that are pertinent to their careers.

Each chapter in this textbook focuses on a topic that is pertinent to diplomatic practice—there are chapters on ceremony and precedence, oratorical and linguistic skill, international law, and multilateral diplomacy. Nevertheless, although the subject matter for each chapter are different, all the chapters have a common objectives which are to provide readers with knowledge about diplomatic practice and to allow them to apply the topics discussed through simulations. Readers will be able to gain insight from history and understand diplomatic practice through the experiences of people in the field and through experiences that they can glean from participating in simulations.-- Back cover.
Includes bibliographical references and index.
In English.
Keywords: Diplomacy -- Study and teaching; International relations -- Study and teaching